Managing pneumonia by community health volunteers: the case of ARI control programme of BRAC, Bangladesh - Hadi, Abdullahel (BRAC Research and Evaluation Division (RED), 2019)
The study examined the role of ARl management practices in improving the competency of community health volunteers in diagnosing and treating pneumonia among children. Data were collected by a group of research physicians who observed the performance ofa sample of 120 health volunteers in Bangladesh where BRAC has been providing community-based ARl control programme in 10 sub-districts since mid 1992. About 1,166 children aged 3-60 months were diagnosed and treated at the households by both the volunteers and physicians. The sensitivity, specificity and overall agreement rates in diagnosing and treating pneumonia were significantly higher among volunteers who had basic training and were regularly supervised. BRAC approach was flexible enough in replacing dropout volunteers by a system of in-service training. Findings revealed that an extended basic training for new entrants, frequent supervision and an integrated programme approach would further improve the programme. The study concludes that the diagnosis and treatment of pneumonia by the community health volunteers were possible at the households in developing countries if intensive basic training and close supervision of the service providers could be ensured.